Kedudukan dan Fungsi Bahasa Indonesia dalam Kehidupan Berbangsa dan Bernegara - tri karyanti (Universitas Aki, 2015)
Malay Indonesian for centuries has become lingua franca in South Asia and has been completely fused with local languages and foreign languages that developed in Indonesia. And on the 28th of October 1928 the Indonesian leaders agreed the language to serve the national language of Indonesia. The Indonesian people, after the rise of the movement in the twentieth century agreed and upheld the language as language of unity. Indonesian language has become the national language and has function as the official language, ranging from the language of instruction in education, a means of communication in daily offices, until the language of cultural development and of modern science and technology. Key word: Indonesian, National Language, the language of unity